THE EFFECT OF EQUALIZATION FUNDS, UNEMPLOYMENT AND POVERTY ON ECONOMIC GROWTH IN BIREUEN REGENCY - Windiyani, Windiyani; Murtala, Murtala (LPPM Universitas Malikussaleh, 2024)
This study aims to determine the effect of equalization funds, unemployment and poverty on economic growth in Bireuen Regency. The data used in this study is skunder data from 2008-2017 obtained from the Central Statistics Agency. The data analysis method used in this study is multiple linear regression. The results showed that partial equalization funds, unemployment and poverty did not have a significant effect on economic growth in Bireuen District. Simultaneously, equalization funds, unemployment and poverty also have no effect on economic growth in Bireuen County.